Pendekatan Multi-Stakeholders Dalam Penanganan Overloading - Gunarta, IGW Samsi; Santoso, Idwan (The ITB Journal Publisher, 2006)
Overloading in freight transport has caused great concern to a number of transport authorities in many countries. A number of efforts, including to intensify load enforcement, deploy load permit scheme, and increase penalty for overloading offences, have been taken. Nevertheless, an optimistic outcome has not showed up to deter such offence to the moment. This paper tried to view another approach in tackling overloading by integrating multistakeholdersâ perspectives in optimising load. It seems that overloading can be explained through the supply and demand concept. However, due to poor previous exploration upon this concept, a number of challenges might have to be faced to deploy the concept properly.Keywords: multi-stakeholders, overloading, freight transport